(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article discusses the scope and relations, similarities and differences of the use of artistic language in anthropocentric proverbs and sayings in Kazakh and Russian. The features of the artistic language found in Kazakh and Russian proverbs are compared. The maximum brevity of proverbs and sayings is determined, the convenience of a brief presentation of thoughts that are the same in both languages. The evidence is given that artistic differences are found in abundance in the Kazakh and Russian languages. During the research, an analysis of many proverbs and sayings in Kazakh and Russian was carried out, examples were given. A special place in modern linguistics, aimed at studying the relationship between language and culture, is occupied by the study of proverbs and sayings, which are the basic ideas of people about values and phenomena in human life. Despite all the differences in any language, most proverbs and sayings are characterized by a clear, accurate, concise transmission of the main idea, whether figuratively or literally. For centuries, people have resorted to certain stylistic means, improving their skills in creating proverbs and sayings to improve emotional coloring, skillful use of objects and phenomena surrounding a person in proverbs and sayings.